2022
DOI: 10.1055/a-1831-5385
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adverse events after endoscopic ultrasound-guided through-the-needle biopsy of pancreatic cysts: a recursive partitioning analysis

Abstract: Background and study aims Endoscopic ultrasound-guided through-the-needle biopsy (TTNB) of pancreatic cystic lesions (PCLs) is associated with a non-negligible risk for adverse events (AEs). We aimed to identify the hierarchic interaction among independent predictors for TTNB-related AEs and to generate a prognostic model using recursive partitioning analysis (RPA). Patients and methods Multicenter retrospective analysis of 506 patients with PCLs who underwent TTNB. RPA of predictors for AEs was performed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…While EUS-FNA may still play a competitive role as compared to EUS-FNB when rapid-on-site cytological evaluation (ROSE) is available, EUS-FNB was found to overperform standard FNA for tissue sampling of several solid lesions in the absence of a pathologist in the endoscopic room [ 3 , 4 , 5 , 6 ]. Moreover, in spite of the favorable diagnostic outcomes of EUS through-the-needle biopsy (TTNB) and confocal laser endomicroscopy (CLE), EUS-FNA is still frequently used in the diagnostic algorithm of cystic pancreatic lesions (PCLs) [ 7 , 8 , 9 ]. Although uncommon, one potential and serious complication of EUS-TA is needle tract seeding (NTS) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While EUS-FNA may still play a competitive role as compared to EUS-FNB when rapid-on-site cytological evaluation (ROSE) is available, EUS-FNB was found to overperform standard FNA for tissue sampling of several solid lesions in the absence of a pathologist in the endoscopic room [ 3 , 4 , 5 , 6 ]. Moreover, in spite of the favorable diagnostic outcomes of EUS through-the-needle biopsy (TTNB) and confocal laser endomicroscopy (CLE), EUS-FNA is still frequently used in the diagnostic algorithm of cystic pancreatic lesions (PCLs) [ 7 , 8 , 9 ]. Although uncommon, one potential and serious complication of EUS-TA is needle tract seeding (NTS) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the cystic neoplasm, such as our case 13, we should keep in mind that EUS-guided through-the-needle biopsy is one of the choices because this method can avoid a hemorrhage into the retroperitoneal cavity after tissue acquisition [ 26 ]. However, a recent study has identified the risk factors and risk classes of an adverse event after EUS-TTNB, and it becomes crucial to select patients before EUS-TTNB to optimize the benefit and risk of this procedure [ 27 ]. Besides, a recent meta-analysis demonstrated that routine use of hemostatic powder is helpful for patients with upper gastrointestinal bleeding, suggestive of the possibility of applying this method to EUS-TA for a subepithelial lesion [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…29,30 A recent multicenter retrospective analysis of 506 patients who underwent TTN biopsy with microforceps revealed that the incidence of adverse events was 11.5%, and intraductal papillary mucinous neoplasms sampled with multiple microforceps passes were classified as being at high risk for adverse events (28%). 31 Therefore, the risk-benefit balance of TTN biopsy should be carefully considered, and TTN biopsy should be performed in selected patients.…”
Section: New Concepts Of Needlesmentioning
confidence: 99%